KnowledgeBoat Logo

Mathematics

Simplify 1sin2 θ1cos2 θ\sqrt{\dfrac{1 - \text{sin}^2 \text{ θ}}{1 - \text{cos}^2 \text{ θ}}}.

Trigonometrical Ratios

19 Likes

Answer

Substituting, 1 - sin2 θ = cos2 θ and 1 - cos2 θ = sin2 θ in 1sin2 θ1cos2 θ\sqrt{\dfrac{1 - \text{sin}^2 \text{ θ}}{1 - \text{cos}^2 \text{ θ}}} we get :

cos2 θsin2 θcot2 θcot θ.\Rightarrow \sqrt{\dfrac{\text{cos}^2 \text{ θ}}{\text{sin}^2 \text{ θ}}} \\[1em] \Rightarrow \sqrt{\text{cot}^2 \text{ θ}} \\[1em] \Rightarrow \text{cot θ}.

Hence, 1sin2 θ1cos2 θ\sqrt{\dfrac{1 - \text{sin}^2 \text{ θ}}{1 - \text{cos}^2 \text{ θ}}} = cot θ.

Answered By

8 Likes


Related Questions